Delay discounting, time perspective, and self-schemas in adolescent alcohol drinking and disordered eating behaviors. (1st January 2022) - Lee, Chia-Kuei; Liao, Li-Ling
Abstract: Delay discounting, time perspective, and self-schemas are well-known predictors of health risk behaviors among adolescents. However, the associations between these constructs and their influence on such behaviors are yet to be examined. This study aimed to determine the relationships among three cognitive constructs, namely, delay discounting, time perspective, and self-schemas, and determine the associations of these constructs with alcohol drinking (alcohol use and alcohol problems) and disordered eating behaviors in adolescents. Participants were 436 eighth-graders from three public junior high schools in southern Taiwan, who answered an anonymous questionnaire assessing self-schema, delay discounting, time perspective, and health risk behaviors. Generalized linear models with robust estimation were performed to estimate the effects; gender was the covariate. Delay discounting was associated with alcohol use (OR = 1.15), but not alcohol problems and disordered eating behaviors. Present-Hedonistic time perspective was associated with alcohol use (OR = 2.01), alcohol problems (IRR = 2.23), and disordered eating behaviors (Exp(b) = 1.38); while Future time perspective was associated with alcohol problems (IRR = 2.18). Drinker self-schema was associated with alcohol use (OR = 1.62) and alcohol problems (IRR = 1.71). Fat/overweight self-schema was associated with overall disordered eating (Exp(b) = 1.03). Thus, the findings suggest that each of the three constructs is independently associated with drinking and disordered eating behaviors, and these associations vary according to the specific type of behavior. Future research identifying the underlying mechanisms linking these constructs to the abovementioned behaviors can be useful for developing targeted intervention strategies.